Positive pole piece, battery and electric device

CN119856294APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380065325.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The dynamic performance of existing lithium-ion batteries is caused by the reduction of pores and ion channels caused by equal pressure of particles and small particle size filling of large particle size gaps in the compound mixing system, resulting in a degradation of battery performance.

Method used

The design of at least two layers of positive electrode active material layers is adopted, wherein the average particle size of the first positive electrode active material and the second positive electrode active material meet R1≥5R2, and the mechanical strength and ionic conduction are improved by layered settings, and the particle size range is limited to optimize Particle matching and porosity.

Benefits of technology

It significantly improves the dynamic performance and energy density of the battery, reduces the impedance growth rate, and improves the lithium ion conduction effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856294A_ABST
    Figure CN119856294A_ABST
Patent Text Reader

Abstract

The invention relates to a positive pole piece, a battery and an electric device. The positive pole piece comprises at least two positive active material layers; two adjacent positive electrode active material layers respectively comprise a first positive electrode active material and a second positive electrode active material; the average particle size of the first positive electrode active material is R1, the average particle size of the second positive electrode active material is R2, and R1 and R2 meet the following relation: R1 > = 5R2. When R1 of the first positive active material and the second positive active material is greater than or equal to 5R2, the positive pole piece comprises at least two positive active material layers, the situation can be relieved to a certain extent by high mechanical strength of active substances with relatively small particle sizes under the same compaction density, gaps among particles with large particle sizes cannot be completely filled, and the service life of the positive pole piece is prolonged. The ion conduction is better than that of a mixed system, and the effects of the two complement each other, so that the battery dynamics can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode, battery, electrical device Technical Field

[0001] The present application relates to a positive electrode sheet, a battery, and an electrical device. Background Art

[0002] In recent years, with the development of lithium-ion secondary battery technology, lithium-ion secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As lithium-ion secondary batteries have achieved great development, higher requirements have been placed on battery dynamic performance and other aspects.

[0003] Summary of the Invention

[0004] The purpose of this application is to provide a positive electrode sheet, a battery, and an electrical device.

[0005] In order to improve the energy density and safety performance of the battery, different active materials are usually mixed and used. That is, different active materials are mixed into a slurry, which is coated on the surface of the current collector to form a mixed active material layer.

[0006] The inventors of the present application have discovered in experiments that when the active material layer contains different materials with greatly different particle sizes, the kinetic performance of the battery is relatively low. However, when materials with different particle sizes are layered, the kinetic performance of the battery is significantly improved.

[0007] The embodiment of the present application is implemented as follows:

[0008] In a first aspect, an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising at least two layers of positive electrode active material;

[0009] The two adjacent positive electrode active material layers include a first positive electrode active material and a second positive electrode active material respectively; the average particle size D of the first positive electrode active material is V 50 is R1, the average particle size D of the second positive electrode active material V 50 is R2, and R1 and R2 satisfy the following relationship:

[0010] R1≥5R2.

[0011] This may be because, when directly physically mixing the first and second positive electrode active materials to form a single positive electrode active material layer, the small particles of the mixed system fill the gaps between large particles, which will reduce pores and ion channels, further reducing battery kinetic performance. However, when the first and second positive electrode active materials R1 ≥ 5R2, the positive electrode plate is provided with at least two layers of positive electrode active material. The high mechanical strength of the active material with smaller particles at the same compaction density will alleviate this problem to a certain extent. In addition, the gaps between the large particles will not be completely filled, and the ion conduction will be better than that of the mixed system. The two effects complement each other, thereby effectively improving battery kinetics.

[0012] In some optional embodiments, 50R2≥R1≥5R2, preferably 35R2≥R1≥5R2.

[0013] In the above technical solution, by further limiting the particle size range of the first positive electrode active material and the second positive electrode active material within the above range, it is beneficial to improve the excessive filling of the large particle size active material with the small particle size material when the particle size difference is too large, resulting in insufficient gaps, reduced porosity, and worsened ionic impedance.

[0014] In some optional embodiments, the value range of R1 is 2 μm-20 μm.

[0015] In some optional embodiments, the value of R1 ranges from 5 μm to 15 μm.

[0016] By limiting the value range of R1 to 2μm-20μm, the particle size of the single layer where the first positive electrode active material is located can be matched with the voids and particle capacity to achieve a better effect, thereby further improving the battery kinetic performance.

[0017] In some optional embodiments, the value of R2 ranges from 0.2 μm to 12 μm.

[0018] In some optional embodiments, the value of R2 ranges from 0.2 μm to 3.6 μm.

[0019] By limiting the value range of R2 to 0.2μm-12μm, the particle size of the single layer where the second positive electrode active material is located can be matched with the voids and particle capacity to achieve a better effect, thereby further improving the battery kinetic performance.

[0020] In some optional embodiments, the first positive electrode active material has 5 μm≤D V 90-D V 10≤20μm; Optionally, the first positive electrode active material has 9≤D V 90-D V 10≤20μm;

[0021] The above mentioned method is to define D in the first positive electrode active material. V 90-D V 10 Within the above range, the particle size of the first positive electrode active material can be increased, thereby improving the energy density of the battery.

[0022] In some optional embodiments, the second positive electrode active material has 5 μm≤D V 90-D V 10≤9μm.

[0023] The above is achieved by limiting the second positive electrode active material to 5 μm ≤ D V 90-D V 10≤9μm, which can increase the particle size of the second positive electrode active material and improve the energy density of the battery.

[0024] In some optional embodiments, the thickness of the positive electrode active material layer where the first positive electrode active material is located is H1; the thickness of the positive electrode active material layer where the second positive electrode active material is located is H2;

[0025] The thickness of H2 accounts for 10%-70% of the total thickness of the positive electrode active layer of the positive electrode sheet.

[0026] The second positive electrode active material has a smaller particle size and a smaller compaction density. By limiting the thickness of H2 to 10%-70% of the total thickness of the positive electrode active layer of the positive electrode sheet, it is beneficial to improve the compaction density of the total positive electrode active layer of the entire positive electrode sheet.

[0027] In some optional embodiments, the first positive electrode active material includes 80%-100% secondary particles by mass.

[0028] Secondary particles are formed by the agglomeration of many primary particles, and there are grain boundaries inside. The transmission of lithium ions within secondary particles can include solid-liquid transmission between small particles and solid-solid transmission within small particles. The internal particles are smaller and the solid-solid transmission path is shorter. The particle size of primary particles is larger than that of the small particles inside the secondary particles. The transmission of lithium ions within primary particles is mainly solid-solid transmission, the path is longer, and the transmission is relatively more difficult.

[0029] The first positive electrode active material includes 80%-100% secondary particles. Active materials with larger particle sizes can provide higher porosity, which is beneficial to the infiltration of the electrolyte, thereby improving the ionic impedance and further improving the battery kinetic performance.

[0030] In some optional embodiments, the second positive electrode active material comprises 95%-100% primary particles by mass.

[0031] The particles in the mixed system are equally compressed because the active materials with large particle sizes are mostly polycrystalline secondary spheres. If the compaction density of the entire electrode design is too high, the secondary spheres may break, resulting in damage to the battery's kinetic performance.

[0032] In the above solution, the second positive electrode active material includes 95%-100% primary particles, which is not only more conducive to the formation of the electrode sheet, but also the small-particle active materials are stacked more densely, which can provide better mechanical strength.

[0033] In some optional embodiments, the first positive electrode active material includes multiple materials, and R1 is D of the multiple materials. V 50;

[0034] or,

[0035] The second positive electrode active material includes a plurality of materials, and R2 is Dv50 of the plurality of materials.

[0036] The first positive electrode active material and the second positive electrode active material include a variety of materials, which can give full play to the advantages of different materials.

[0037] In some optional embodiments, the first positive electrode active material includes a layered structure positive electrode material.

[0038] By limiting the first active material to include a layered structure positive electrode material, the layered structure positive electrode material has a larger particle size, and the large particle size active material provides higher energy density and porosity, which is beneficial to the infiltration of the electrolyte, thereby facilitating the improvement of ionic impedance.

[0039] In some optional embodiments, the first positive electrode active material includes at least one of a nickel cobalt manganese oxide ternary material, a nickel cobalt aluminum oxide ternary material, and a nickel cobalt manganese aluminum oxide ternary material, or includes at least one of doped or coated materials of the above ternary materials.

[0040] In some optional embodiments, the second positive electrode active material includes at least one of a spinel structure positive electrode material or an olivine structure positive electrode material.

[0041] By limiting the first active material to include at least one of a spinel structure positive electrode material or an olivine structure positive electrode material, the spinel structure positive electrode material or the olivine structure positive electrode material has a smaller particle size and is stacked more densely, which can improve better mechanical strength, has more grain boundaries, and is also conducive to infiltration. When combined with a layered structure positive electrode material in a layered design, the battery kinetic performance can be effectively improved.

[0042] In some optional embodiments, the second positive electrode active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, and modified doped lithium manganese iron phosphate;

[0043] Optionally, the chemical formula of the modified doped lithium manganese iron phosphate includes: LiMPO4, where M includes Mn and non-Mn elements;

[0044] Optionally, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is a manganese doping element, and the second doping element is a phosphorus doping element;

[0045] Optionally, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge;

[0046] Optionally, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg;

[0047] Optionally, the second doping element includes one or more elements selected from B, S, Si and N;

[0048] Optionally, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and R includes one or more elements selected from the group consisting of B, S, Si, and N;

[0049] Optionally, the second positive electrode active material includes Li a A e Mn 1-f B f P 1-g C g O 4-n D n ;

[0050] wherein A comprises one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W;

[0051] B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge;

[0052] C includes one or more elements selected from B, S, Si and N;

[0053] D includes one or more elements selected from the group consisting of S, F, Cl, and Br;

[0054] a is selected from the range of 0.9 to 1.1, e is selected from the range of 0.001 to 0.1, f is selected from the range of 0.001 to 0.5, g is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the second positive active material is electrically neutral.

[0055] The particle size of the above positive electrode materials is relatively small. When used in combination with materials with larger particle sizes such as ternary materials, the solution of the embodiment of the present application can effectively improve the battery dynamics performance.

[0056] In some optional embodiments, the positive electrode sheet includes a current collector;

[0057] At least two positive electrode active material layers are stacked in sequence and formed on the surface of the current collector, and the porosity of the at least two positive electrode active material layers decreases in sequence in a direction away from the current collector.

[0058] At least two active material layers are stacked in sequence on the surface of the current collector, and the porosity of the at least two active material layers decreases in sequence as they move away from the current collector, so that the electrolyte and the positive electrode plate can be fully infiltrated, ensuring that the conduction of lithium ions is not affected.

[0059] In some optional embodiments, the porosity of the positive electrode active material layer in contact with the current collector is ≥45%; optionally, the porosity of the positive electrode active material layer in contact with the current collector is ≥60%.

[0060] Within the above ratio range, the lithium ion conduction effect is enhanced.

[0061] In some optional embodiments, the porosity of the outermost positive electrode active material layer is ≥35%; optionally, the porosity of the outermost positive electrode active material layer is ≥50%.

[0062] Within the above ratio range, the lithium ion conduction effect is further improved.

[0063] In a second aspect, an embodiment of the present application provides a battery, which includes the positive electrode plate provided in the first aspect.

[0064] In the above technical solution, the battery has better dynamic performance by being provided with the positive electrode plate provided by the first aspect.

[0065] In a third aspect, an embodiment of the present application provides an electrical device, which includes the positive electrode plate provided in the second aspect.

[0066] In the above technical solution, the electrical device has better dynamic performance by being equipped with the battery provided by the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.

[0068] FIG1 is a schematic structural diagram of a vehicle provided in some embodiments of the present application;

[0069] FIG2 is an exploded view of a battery provided in some embodiments of the present application;

[0070] FIG3 is an exploded view of the battery cell shown in FIG2 ;

[0071] FIG4 is a schematic diagram of a partial structure of an electrode assembly provided in some embodiments of the present application;

[0072] FIG5 is a schematic diagram of a partial structure of a positive electrode plate provided in some embodiments of the present application.

[0073] icon:

[0074] Vehicles 1000;

[0075] Battery 100; Controller 200; Motor 300;

[0076] Box body 10; first part 11; second part 12; accommodating space 13;

[0077] Battery cell 20; housing 21; electrode assembly 22; electrode terminal 23; pressure relief structure 24;

[0078] Housing 211; cover 212; positive electrode sheet 221; negative electrode sheet 222; separator 223;

[0079] Positive electrode current collector 2211; positive electrode active material layer 2212;

[0080] Negative electrode current collector 2221; negative electrode positive electrode active material layer 2222. DETAILED DESCRIPTION

[0081] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0082] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0083] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0084] In the description of the embodiments of the present application, the orientations or positional relationships indicated by technical terms such as "inside" and "outside" are based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present application.

[0085] In the description of the embodiments of this application, unless otherwise specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; they can refer to direct connections or indirect connections through an intermediate medium. Those skilled in the art will understand the specific meanings of the above terms in the embodiments of this application based on specific circumstances.

[0086] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0087] In the embodiments of this application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components in different embodiments are omitted. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of this application, as well as the overall heights, lengths, widths, and other dimensions of the integrated device shown in the drawings are merely illustrative and do not constitute any limitation on this application.

[0088] Batteries made from positive electrode sheets obtained by physically mixing different active materials have poor kinetic performance. The reason is analyzed as follows: the particles in the mixed system are equally compressed, the large-particle active materials are mostly polycrystalline secondary spheres, and the compaction density of the entire electrode design is too high, resulting in the breakage of the secondary spheres and impaired performance; and the filling of large-particle gaps with small particles in the mixed system will reduce the pores and ion channels, thereby leading to poor battery kinetic performance.

[0089] The embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising at least two active material layers;

[0090] The two adjacent active material layers include a first positive electrode active material and a second positive electrode active material respectively; the average particle size D of the first positive electrode active material is V 50 is R1, the average particle size D of the second positive electrode active material V 50 is R2, and R1 and R2 satisfy the following relationship:

[0091] R1≥5R2.

[0092] By adopting the above-mentioned positive electrode sheet, the dynamic performance of the battery can be improved.

[0093] The electrical device comprising the battery has more excellent dynamic performance.

[0094] For the convenience of description, the following embodiments are described using a lithium-ion battery according to an embodiment of the present application as an example. A vehicle according to an embodiment of the present application is also described as an example of an electrical device.

[0095] Refer to Figure 1, which is a structural schematic diagram of a vehicle 1000 provided in some embodiments of the present application. The vehicle 1000 can be a fuel vehicle, a gas vehicle or a new energy vehicle. The new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 can be provided at the bottom, head or tail of the vehicle 1000. The battery 100 can be used to power the vehicle 1000. For example, the battery 100 can serve as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0096] In some embodiments of the present application, the battery 100 can not only serve as the operating power source of the vehicle 1000, but also serve as the driving power source of the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0097] In this application, battery 100 refers to a single physical module that includes one or more battery cells 20 to provide voltage and capacity. Battery 100 generally includes a housing 10 for enclosing one or more battery cells 20. Housing 10 prevents liquids or other foreign matter from affecting the charging or discharging of battery cells 20.

[0098] Referring to Figure 2, which is an exploded view of a battery 100 provided in some embodiments of the present application, the battery 100 may include a housing 10 and a battery cell 20, with the battery cell 20 housed within the housing 10. The housing 10 is used to house the battery cell 20 and may have various structures. In some embodiments, the housing 10 may include a first portion 11 and a second portion 12, which overlap each other and together define a storage space 13 for accommodating the battery cell 20. The second portion 12 may be a hollow structure with one end open, and the first portion 11 may be a plate-like structure, which overlaps the open side of the second portion 12 to form the housing 10 with the storage space 13. Alternatively, the first portion 11 and the second portion 12 may both be hollow structures with one end open, with the open side of the first portion 11 overlapping the open side of the second portion 12 to form the housing 10 with the storage space 13. Of course, the first portion 11 and the second portion 12 may have various shapes, such as a cylinder, a rectangular parallelepiped, etc.

[0099] In the battery 100, there can be one or more battery cells 20. If there are multiple battery cells 20, the multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection. Mixed connection means that the multiple battery cells 20 are connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the case 10. Alternatively, multiple battery cells 20 can be first connected in series, in parallel, or in a mixed connection to form a module, and the multiple modules are then connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the case 10. The battery 100 can also include other structures. For example, the multiple battery cells 20 can be electrically connected through a busbar component to achieve parallel, series, or mixed connection of the multiple battery cells 20.

[0100] Each battery cell 20 may be a lithium-ion battery, such as a secondary battery or a primary battery; it may also be a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited thereto.

[0101] Referring to Figure 3 , which is an exploded view of the battery cell 20 shown in Figure 2 , the battery cell 20 is the smallest unit that makes up the battery 100. The battery cell 20 may include a housing 21 , an electrode assembly 22 , and an electrolyte, with both the electrode assembly 22 and the electrolyte being housed within the housing 21 .

[0102] The outer shell 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space of the battery cell 20, wherein the formed sealed space can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211. Functional components such as electrode terminals 23 and pressure relief structures 24 can also be provided on the cover 212. A sealing ring can be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.

[0103] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The material of the shell 211 and the cover 212 can be various, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The material of the sealing ring can be various, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.

[0104] Referring to Figure 4 , the electrode assembly 22 may be composed of a positive electrode sheet 221, a negative electrode sheet 222, and a separator 223. The separator 223 is located between the positive electrode sheet 221 and the negative electrode sheet 222 to provide isolation. The electrode assembly 22 may be a wound or laminated structure, but the present invention is not limited thereto.

[0105] 4 , the negative electrode sheet 222 includes a negative electrode current collector 2221 and a negative electrode positive active material layer 2222. The negative electrode current collector 2221 may be made of copper, and the negative electrode positive active material layer 2222 includes a negative electrode active material. The negative electrode active material includes at least one of graphite, silicon, a silicon alloy, or a tin alloy.

[0106] 5 , the positive electrode sheet 221 includes a positive current collector 2211 and a positive active material layer 2212 . Taking the lithium-ion battery cell 20 as an example, the positive current collector 2211 may be made of aluminum. The positive active material layer 2212 includes positive active materials.

[0107] The positive electrode sheet 221 includes at least two positive electrode active material layers 2212 .

[0108] Furthermore, the two adjacent positive electrode active material layers 2212 include a first positive electrode active material and a second positive electrode active material respectively; the average particle size D of the first positive electrode active material is V 50 is R1, the average particle size D of the second positive electrode active material V 50 is R2, and R1 and R2 satisfy the following relationship:

[0109] R1≥5R2.

[0110] Directly physically mixing the first and second positive electrode active materials to form a single positive electrode active material layer, where small particles fill the gaps between larger particles in a physical mixture, reduces porosity, reduces ion channels, and further degrades battery kinetics. However, when the R1 of the first and second positive electrode active materials is greater than or equal to 5R2, the positive electrode plate 221 comprises at least two positive electrode active material layers 2212. The high mechanical strength of the smaller active material at the same compaction density alleviates this problem to some extent. Furthermore, the gaps between the larger particles are not completely filled, resulting in better ion conduction than in a physical mixture. These two effects complement each other, effectively improving battery kinetics. It should be noted that when the R1 of the first and second positive electrode active materials is greater than or equal to 5R2, the positive electrode plate 221 comprises at least two positive electrode active material layers 2212, with a clear boundary formed between adjacent positive electrode active material layers 2212.

[0111] The above DV50 means: when the active material particles are accumulated from small to large, when the accumulated active material particles account for 50% of the total volume, the particle size of the active material particles is less than a certain value, and this value is the Dv50 value.

[0112] Furthermore, in some embodiments of the present application, 50R2≥R1≥5R2.

[0113] Further preferably, in some embodiments of the present application, 35R2≥R1≥5R2.

[0114] By further limiting the particle size range of the first positive electrode active material and the second positive electrode active material to the above range, it is beneficial to improve the overfilling of the large particle size active material with the small particle size material when the particle size difference is too large, resulting in insufficient voids, reduced porosity, and worsened ionic impedance. Furthermore, in some embodiments of the present application, the value range of R1 is 2μm-20μm. Further optionally, in some embodiments of the present application, the value range of R1 is 5μm-15μm.

[0115] By limiting the value range of R1 to 2μm-20μm, the particle size of the single layer where the first positive electrode active material is located can be matched with the voids and particle capacity to achieve a better effect, thereby further improving the battery kinetic performance.

[0116] Illustratively, in some embodiments of the present application, the value of R1 is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0117] Furthermore, in some embodiments of the present application, the value range of R2 is 0.2 μm-12 μm. Further optionally, in some embodiments of the present application, the value range of R2 is 0.2 μm-3.6 μm.

[0118] By limiting the value range of R2 to 0.2μm-12μm, the particle size of the second positive electrode active material in the single layer can be matched with the voids and particle capacity to achieve a better effect, thereby further improving the battery kinetic performance.

[0119] Illustratively, in some embodiments of the present application, the value of R2 is 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or 3.5 μm.

[0120] Furthermore, in some embodiments of the present application, the first positive electrode active material has a thickness of 5 μm ≤ D V 90-D V 10≤20μm. Further optionally, in the first positive electrode active material, 9≤D V 90-D V 10≤20μm.

[0121] In the above embodiment, Dv90 means: when the first positive electrode active material particles are accumulated from small to large, when the accumulation accounts for 90% of the total volume, the particle size of the first positive electrode active material particles is less than a certain value, and the value is the value of Dv90; Dv10 means: when the first positive electrode active material particles are accumulated from small to large, when the accumulation accounts for 10% of the total volume, the particle size of the first positive electrode active material particles is less than a certain value, and the value is the value of Dv10.

[0122] The above mentioned method is to define D in the first positive electrode active material. V 90-D V 10 Within the above range, the particle size of the first positive electrode active material can be increased, thereby improving the energy density of the battery.

[0123] Further optionally, in some embodiments of the present application, the second positive electrode active material has 5 μm≤D V 90-D V 10≤9μm.

[0124] In the above embodiment, Dv90 means: when the second positive electrode active material particles are accumulated from small to large, when the accumulation accounts for 90% of the total volume, the particle size of the second positive electrode active material particles is less than a certain value, and the value is the value of Dv90; Dv10 means: when the second positive electrode active material particles are accumulated from small to large, when the accumulation accounts for 90% of the total volume, the particle size of the second positive electrode active material particles is less than a certain value, and the value is the value of Dv90.

[0125] The above is achieved by limiting the second positive electrode active material to 5 μm ≤ D V 90-D V 10≤9μm, which can increase the particle size of the second positive electrode active material and improve the energy density of the battery.

[0126] According to the embodiments of the present application, the aforementioned Dv10, Dv50 or Dv90 is determined by a particle size analyzer-laser diffraction method. Specifically, reference can be made to the standard GB / T 19077-2016, and the measurement can be performed using a laser diffraction scattering particle size analyzer according to the manufacturer's instructions.

[0127] Furthermore, in some embodiments of the present application, the thickness of the positive electrode active material layer where the first positive electrode active material is located is H1; the thickness of the positive electrode active material layer where the second positive electrode active material is located is H2;

[0128] The thickness of H2 accounts for 10%-70% of the total thickness of the positive electrode active layer of the positive electrode sheet. The second positive electrode active material has a smaller particle size and a lower compaction density. By limiting the thickness of H2 to 10%-70% of the total thickness of the positive electrode active layer of the positive electrode sheet, the compaction density of the total positive electrode active layer of the entire positive electrode sheet is improved.

[0129] Further optionally, the thickness of H2 accounts for 11%-69% of the total thickness of the positive electrode active layer of the positive electrode sheet.

[0130] Illustratively, in some embodiments of the present application, the thickness of the above-mentioned H2 accounts for 12%, 13%, 15%, 18%, 20%, 25%, 28%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65% of the total thickness of the positive electrode active layer of the positive electrode sheet.

[0131] Furthermore, in some embodiments of the present application, the first positive electrode active material includes 80%-100% secondary particles, and the rest are primary particles, calculated by mass percentage.

[0132] Secondary particles are formed by the agglomeration of many primary particles, and there are grain boundaries inside. The transmission of lithium ions within secondary particles can include solid-liquid transmission between small particles and solid-solid transmission within small particles. The internal particles are smaller and the solid-solid transmission path is shorter. The particle size of primary particles is larger than that of the small particles inside the secondary particles. The transmission of lithium ions within primary particles is mainly solid-solid transmission, the path is longer, and the transmission is relatively more difficult.

[0133] The first positive electrode active material includes 80%-100% secondary particles. The larger particle size active material can provide higher porosity, which is beneficial to the infiltration of the electrolyte, thereby improving the ionic impedance and further improving the battery kinetic performance.

[0134] Further optionally, in some embodiments of the present application, the first positive electrode active material includes 81%-99% secondary particles, and the rest are primary particles, based on mass percentage.

[0135] Further optionally, in some embodiments of the present application, the first positive electrode active material includes 85%-95% secondary particles, and the rest are primary particles, calculated by mass percentage.

[0136] Illustratively, in some embodiments of the present application, the first positive electrode active material includes 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93% or 94% secondary particles by mass; the rest are primary particles.

[0137] Furthermore, in some embodiments of the present application, the second positive electrode active material includes 95%-100% primary particles, and the rest are secondary particles, in terms of mass percentage.

[0138] The particles in the mixed system are equally compressed because the active materials with large particle sizes are mostly polycrystalline secondary spheres. If the compaction density of the entire electrode design is too high, the secondary spheres may break, resulting in damage to the battery's kinetic performance.

[0139] In the above solution, the second positive electrode active material includes 95%-100% primary particles, which is not only more conducive to the formation of the electrode sheet, but also the small-particle active materials are stacked more densely, which can provide better mechanical strength.

[0140] Further optionally, in some embodiments of the present application, the second positive electrode active material includes 96%-100% primary particles, and the rest are secondary particles, calculated by mass percentage.

[0141] For example, in some embodiments of the present application, the second positive electrode active material includes 97%, 98%, 99% or 100% primary particles by mass; the rest are secondary particles.

[0142] Furthermore, in some embodiments of the present application, the first positive electrode active material includes multiple materials, and R1 is the average particle size D of the multiple materials. V 50; or

[0143] The second positive electrode active material includes a plurality of materials, and R2 is Dv50 of the plurality of materials.

[0144] The first positive electrode active material and the second positive electrode active material include a variety of materials, which can give full play to the advantages of different materials.

[0145] Further, in some embodiments of the present application, the first active material includes a layered structure positive electrode material.

[0146] By limiting the first active material to include a layered structure positive electrode material, the layered structure positive electrode material has a larger particle size, and the large particle size active material provides higher energy density and porosity, which is beneficial to the infiltration of the electrolyte, thereby facilitating the improvement of ionic impedance.

[0147] Furthermore, in some embodiments of the present application, the first positive electrode active material includes at least one of a nickel-cobalt-manganese oxide ternary material, a nickel-cobalt-aluminum oxide ternary material, and a nickel-cobalt-manganese oxide ternary material, or includes at least one of a doped or coated material of the above ternary materials. Furthermore, in some embodiments of the present application, the second positive electrode active material includes at least one of a spinel structure positive electrode material or an olivine structure positive electrode material.

[0148] By limiting the first active material to include at least one of a spinel structure positive electrode material or an olivine structure positive electrode material, the spinel structure positive electrode material or the olivine structure positive electrode material has a smaller particle size and is stacked more densely, which can improve better mechanical strength, has more grain boundaries, and is also conducive to infiltration. When combined with a layered structure positive electrode material in a layered design, the battery kinetic performance can be effectively improved.

[0149] Furthermore, in some embodiments of the present application, the second positive electrode active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, and modified and doped lithium manganese iron phosphate.

[0150] Furthermore, in some embodiments of the present application, the chemical formula of the modified doped lithium manganese iron phosphate includes: LiMPO4, where M includes Mn and non-Mn elements.

[0151] LiMPO4 is not a specific molecular structure formula, but a general expression of lithium manganese phosphate.

[0152] Furthermore, in some embodiments of the present application, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is a manganese doping element, and the second doping element is a phosphorus doping element.

[0153] Furthermore, in some embodiments of the present application, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge.

[0154] Furthermore, in some embodiments of the present application, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg.

[0155] Furthermore, in some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si, and N.

[0156] Furthermore, in some embodiments of the present application, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0157] Furthermore, in some embodiments of the present application, the second positive electrode active material includes Li a A e Mn 1-f B f P 1-g C g O 4-n D n ;

[0158] wherein A comprises one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W;

[0159] B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge;

[0160] C includes one or more elements selected from B, S, Si and N;

[0161] D includes one or more elements selected from the group consisting of S, F, Cl, and Br;

[0162] a is selected from the range of 0.9 to 1.1, e is selected from the range of 0.001 to 0.1, f is selected from the range of 0.001 to 0.5, g is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the second positive active material is electrically neutral.

[0163] In some embodiments, the compound Li a A e Mn 1-f B f P 1-g C g O 4-n D n The preparation method may include the following steps:

[0164] (1) dissolving a manganese source, a source of element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with element A;

[0165] (2) adding a lithium source, a phosphorus source, an element R source, a solvent, and the manganese salt doped with element A obtained in step (1) into a reaction vessel, grinding and mixing to obtain a slurry;

[0166] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;

[0167] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.

[0168] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.

[0169] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and organic acids such as oxalic acid, and may be, for example, oxalic acid. The source of element R is selected from at least one of sulfates, borates, nitrates, and silicates of element R. The source of element A is selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate, and sulfate of A.

[0170] In some embodiments, the positive electrode active material includes Li a A e Mn 1-f B f P 1-g C g O 4-n D n, wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, C includes one or more elements selected from the group consisting of B, S, Si, and N, D includes one or more elements selected from the group consisting of S, F, Cl, and Br, a is selected from the range of 0.9 to 1.1, e is selected from the range of 0.001 to 0.1, f is selected from the range of 0.001 to 0.5, g is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the positive electrode active material is electrically neutral.

[0171] It should be noted that Li a A e Mn 1-f B f P 1-g C g O 4-n D n The compound is actually a specific LiMPO4 material. Its preparation method can refer to Li a A e Mn 1-f B f P 1-g C g O 4-n D n , no limitation is made here.

[0172] In some embodiments, the positive electrode active material further has a coating layer comprising carbon.

[0173] The introduction of a carbon-containing coating layer improves the conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually a core-shell structure with LiMPO4 as the core and the surface of the core covered with the coating layer.

[0174] The battery is accompanied by Li deintercalation and consumption during the charging and discharging process, and the molar content of Li is different when the battery is discharged to different states.

[0175] In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before adding the material. When the positive electrode material is used in a battery system, the molar content of Li will change after charge and discharge cycles.

[0176] In addition, the preparation process and conditions of the materials are different, and the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y A y P 1-z R z The molar content of the O element in O4 is not strictly 4.

[0177] The particle size of the above positive electrode materials is relatively small. When used in combination with materials with larger particle sizes such as ternary materials, the solution of the embodiment of the present application can effectively improve the battery dynamics performance.

[0178] Furthermore, in some embodiments of the present application, the positive electrode sheet includes a current collector;

[0179] At least two active material layers are stacked in sequence and formed on the surface of the current collector, and the porosity of the at least two active material layers decreases in sequence in a direction away from the current collector.

[0180] At least two active material layers are stacked in sequence on the surface of the current collector, and the porosity of the at least two active material layers decreases in sequence as they move away from the current collector, so that the electrolyte and the positive electrode plate can be fully infiltrated, ensuring that the conduction of lithium ions is not affected.

[0181] Furthermore, in some embodiments of the present application, the porosity of the active material layer in contact with the current collector is ≥45%.

[0182] Within the above ratio range, the lithium ion conduction effect is enhanced.

[0183] Further optionally, in some embodiments of the present application, the porosity of the active material layer in contact with the current collector is ≥60%.

[0184] Illustratively, the porosity of the positive active material layer contacting the positive current collector is 46%, 50%, 55%, 65% or 70%.

[0185] Furthermore, in some embodiments of the present application, the porosity of the outermost active material layer is ≥35%.

[0186] Within the above ratio range, the lithium ion conduction effect is further improved.

[0187] Further optionally, the porosity of the outermost active material layer is ≥50%.

[0188] Illustratively, the porosity of the outermost positive electrode active material layer is 36%, 40%, 40%, 55% or 65%.

[0189] According to the embodiments of the present application, the porosity can be determined by the gas replacement method. Specifically, according to the embodiments of the present application, it can be determined by referring to GB / T 24586-2009 through the following steps: immerse the electrode in dimethyl carbonate (DMC), clean and dry it. If it is a fresh electrode, it does not need to be cleaned. Put the sample into the sample cup, record the number of samples to calculate the apparent volume, place the sample in the true density tester, and measure the true volume using the gas replacement method. The electrode porosity is the percentage of the pore volume in the electrode to the total volume of the electrode. The calculation formula is: Porosity = (V V0) / V × 100%, where V0 is the true volume and V is the apparent volume; Apparent volume V = S*H*A, S is the surface area of ​​the electrode, H is the thickness of the electrode, and A is the number of electrode samples.

[0190] Furthermore, in some embodiments of the present application, the mass ratio of the active material in each positive electrode active material layer to the total positive electrode active material of the positive electrode sheet is 10%-90%.

[0191] By controlling the active material in each positive electrode active material layer to account for 10%-90% of the total positive electrode active material of the positive electrode sheet, a positive electrode active material layer with an optimal thickness can be obtained to ensure the battery dynamics performance.

[0192] Further optionally, the mass ratio of the active material in each positive electrode active material layer to the total positive electrode active material of the positive electrode sheet is 15%-85%.

[0193] Illustratively, the mass ratio of the active material in each positive electrode active material layer to the total positive electrode active material of the positive electrode sheet is: 20%, 30%, 40%, 50%, 60%, 70% or 80%.

[0194] Furthermore, in some embodiments of the present application, the active material layer further includes a conductive agent and a binder;

[0195] Calculated by mass percentage, the active material is 89%-98%; the conductive agent is 0.4%-5%; and the binder is 0.6%-6%.

[0196] Within the above ratio range, a positive electrode active material slurry with excellent comprehensive performance can be obtained.

[0197] Further optionally, in some embodiments of the present application, in terms of mass percentage, the active material is 90%-97%; the conductive agent is 0.5%-4.8%; and the binder is 0.7%-5.9%.

[0198] Illustratively, in terms of mass percentage, the active material is 91%, the conductive agent is 4%, and the binder is 5%; or in terms of mass percentage, the active material is 95%, the conductive agent is 1%, and the binder is 4%; or in terms of mass percentage, the active material is 96%, the conductive agent is 0.5%, and the binder is 3.5%.

[0199] Some specific embodiments are listed below to better illustrate the present application.

[0200] Second positive electrode active material

[0201] A. Compound LiMn 0.22 Fe 0.78 The preparation method of PO4 includes:

[0202] Step S1: Preparation of Fe-doped manganese oxalate

[0203] 252.9g of manganese carbonate and 903.7g of ferrous carbonate were added to a mixer and thoroughly mixed for 6 hours. The resulting mixture was then transferred to a reactor, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added. The mixture was heated to 80°C and stirred at 500 rpm for 6 hours, mixing until the reaction terminated and no bubbles were generated, resulting in an Fe-doped manganese oxalate suspension. The suspension was then filtered, dried at 120°C, and sand-milled to obtain ferromanganese oxalate particles with a particle size of 100nm.

[0204] Step S2: Preparation of LiMn 0.22 Fe 0.78 PO4

[0205] Take the manganese oxalate iron (C2O4Mn 0.22 Fe 0.78 1791.4 g of 2H2O (calculated as 2H2O), 369.4 g of lithium carbonate, and 1150.1 g of ammonium dihydrogen phosphate were added to 20 L of deionized water, stirred thoroughly, and uniformly mixed at 80°C for 10 hours to obtain a slurry. The slurry was transferred to a spray dryer for spray drying and granulation, and then dried at 250°C to obtain a powder. The powder was sintered in a roller kiln at 700°C for 4 hours in a protective atmosphere (90% nitrogen and 10% hydrogen).

[0206] Carbon-coated LiMn 0.22 Fe 0.78 The preparation method of PO4 includes:

[0207] Take the manganese oxalate iron (C2O4Mn 0.22 Fe 0.781791.4 g of 1% nitric acid (based on 2H2O), 369.4 g of lithium carbonate, 1150.1 g of ammonium dihydrogen phosphate, and 0.005 mol of sucrose were added to 20 L of deionized water, stirred thoroughly, and uniformly mixed at 80°C for 10 hours to obtain a slurry. The slurry was transferred to a spray dryer for spray drying and granulation, and then dried at 250°C to obtain a powder. The powder was sintered in a roller kiln at 700°C for 4 hours in a protective atmosphere (90% nitrogen and 10% hydrogen).

[0208] The preparation steps of other undoped lithium manganese iron phosphate materials are the same as those of the aforementioned compound A, with the only difference being that the contents of manganese carbonate and ferrous carbonate are changed to satisfy the molar ratio of manganese to iron in the chemical formula of the corresponding compound.

[0209] You can also buy it directly from the market.

[0210] B. Compound Li 1.001 Mn 0.999 Fe 0.001 P 0.999 Si 0.001 The preparation method of O4 includes:

[0211] Step S1: Preparation of Fe-doped manganese oxalate

[0212] 1148.2g of manganese carbonate and 1.2g of ferrous carbonate were added to a mixer and thoroughly mixed for 6 hours. The resulting mixture was then transferred to a reactor, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added. The mixture was heated to 80°C and stirred at 500 rpm for 6 hours, mixing until the reaction terminated and no bubbles were generated, resulting in an Fe-doped manganese oxalate suspension. The suspension was then filtered, dried at 120°C, and sand-milled to obtain ferromanganese oxalate particles with a particle size of 100nm.

[0213] Step S2: Preparation of Li 1.001 Mn 0.999 Fe 0.001 P 0.999 Si 0.001 O4

[0214] Take the manganese oxalate iron (C2O4Mn 0.999 Fe 0.0011789.6 g of 2H2O (calculated as 2H2O), 369.8 g of lithium carbonate, 1148.9 g of ammonium dihydrogen phosphate, and 0.8 g of silicic acid were added to 20 L of deionized water, stirred thoroughly, and uniformly mixed at 80°C for 10 hours to obtain a slurry. The slurry was transferred to a spray dryer for spray drying and granulation, and then dried at 250°C to obtain a powder. The powder was sintered in a roller kiln at 700°C for 4 hours in a protective atmosphere (90% nitrogen and 10% hydrogen).

[0215] The preparation steps of lithium manganese iron phosphate materials doped with other elements (such as Ti) are the same as the preparation steps of the aforementioned compound B. The only difference is that silicic acid is replaced as the source of the corresponding element (such as titanium tetrachloride) and the raw material ratio is adjusted to meet the molar ratio in the chemical formula of the corresponding compound.

[0216] It can also be purchased directly from the market.

[0217]

First positive electrode active material

[0218] The layered structure positive electrode material was purchased from the market.

[0219] Example 1

[0220] 1) Preparation of positive electrode sheet

[0221] The aforementioned first positive electrode active material is mixed with a conductive agent and a binder in a certain mass ratio and dispersed in N-methylpyrrolidone to form a first positive electrode active material slurry. The average particle size of the first positive electrode active material is R1. The first positive electrode active material and its parameters are shown in Table 1.

[0222] The aforementioned second positive electrode active material is selected, mixed with a conductive agent and a binder in a certain mass ratio, and dispersed in N-methylpyrrolidone to prepare a second positive electrode active material slurry; wherein the average particle size of the second positive electrode active material is R2.

[0223] The first positive electrode active material slurry prepared above is coated on the surfaces of both sides of the aluminum foil. At the same time, the second positive electrode active material slurry prepared above is coated on the surface of the positive electrode coated with the first positive electrode active material slurry to obtain a positive electrode plate. The mass proportion of the first positive electrode active material and the second positive electrode active material in the active material layer of the positive electrode plate is 50% respectively.

[0224] 2) Preparation of negative electrode sheet

[0225] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly in deionized water at a weight ratio of 90:5:2:2:1, coated on copper foil, dried, and cold pressed to obtain the negative electrode sheet. The coating amount was 0.2g / cm 2 , compacted density is 1.7g / cm 3 .

[0226] 3) Preparation of diaphragm

[0227] The polyethylene film is used as the substrate, and a coating is applied on the substrate to prepare the diaphragm.

[0228] 4) Preparation of lithium-ion batteries

[0229] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to separate them. The cells are then wound to form a bare cell. The bare cell is placed in an outer packaging, injected with electrolyte, and sealed to form a battery. The electrolyte consists of a solution of 1 mol / L LiPF6 in a 1:1:1 volume ratio of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC).

[0230] The differences between Example 2-35 and Example 1 are shown in Table 1 and Table 2.

[0231] Example 36 differs from Example 1 in that, in step 1) of Example 1, the second positive electrode active material slurry is first applied to both surfaces of the aluminum foil, and then the first positive electrode active material slurry is applied to the surface of the second positive electrode active material slurry. Other preparation parameters are shown in Tables 1 and 2.

[0232] Comparative Example 1

[0233] The only difference from Example 1 is step 1) preparation of the positive electrode sheet: in Comparative Example 1, the first positive electrode active material slurry and the second positive electrode active material slurry are mixed evenly and then coated on the surfaces of both sides of the aluminum foil; the mass proportions of the first positive electrode active material and the second positive electrode active material are also 50% respectively.

[0234] The differences between the other comparative examples and comparative example 1 are shown in Table 1 and Table 2.

[0235] Detection method:

[0236] Dynamic performance test method: At 25°C, the hard-shell battery is first fully discharged at 0.3C and then tested. The test process is as follows: the hard-shell battery is charged at a constant current of 0.3C to a voltage of 4.25V, then charged at a constant voltage of 4.25V to a current of 0.02C. After standing for 10 minutes, the lithium-ion battery is discharged at a constant current of 0.3C to a voltage of 2.5V. This is a charge and discharge cycle process. The voltage drop in the first 30 seconds of this discharge is divided by the discharge current and recorded as the resistance value of the first cycle. The hard-shell battery is subjected to 500 cycles of charge and discharge tests according to the above method. The ratio of the discharge voltage drop in the first 30 seconds of the hard-shell battery to the discharge current in the 500th cycle is recorded, that is, the resistance value of the 500th cycle. The ratio of the impedance difference between the 500th cycle and the first cycle to the impedance of the first cycle (impedance growth rate) can be used to characterize the dynamic performance.

[0237] The performance of the lithium-ion batteries of various embodiments and comparative examples was tested, and the results are shown in Table 3.

[0238] Table 1

[0239] Table 2

[0240] Table 3 Battery performance

[0241] From the test results in Table 3 above, it can be seen that:

[0242] In the embodiment of the present application, the impedance growth rate (the ratio of the impedance difference between the 500th cycle and the first cycle to the impedance of the first cycle) ranged from 3.4% to 78.6%. In contrast, the impedance growth rate of Comparative Example 1 (the ratio of the impedance difference between the 500th cycle and the first cycle to the impedance of the first cycle) reached 87.5%. The lower the ratio, the better the kinetic performance. This shows that the solution of the present application effectively improves the kinetic performance of the battery.

[0243] Further, it can be seen from Examples 1-6, 8-10, 12-26, and 32-34 that when

[0244] 35R2≥R1≥5R2, the solution of the present application can further improve the dynamic performance of the battery.

[0245] Furthermore, it can be seen from Examples 24 to 32 that the particle size distribution of the first positive electrode active material satisfies: when DV90-DV10>20 μm, the improvement in the kinetic performance of the battery is moderate; the particle size distribution of the first positive electrode active material satisfies:

[0246] When 9μm≤DV90-DV10≤20μm, the battery's kinetic performance is greatly improved.

[0247] Furthermore, in Example 13, the first positive electrode active material uses primary particles, and the second positive electrode active material uses primary particles, and the kinetic performance (ratio of the impedance difference between the 500th cycle and the first cycle to the impedance of the first cycle) is 33.4%;

[0248] In Example 4, the first positive electrode active material is a secondary particle, and the second positive electrode active material is a primary particle. The kinetic performance (the ratio of the impedance difference between the 500th cycle and the first cycle to the impedance of the first cycle) is 17.5%;

[0249] From the comparison between the two, it can be seen that the first positive electrode active material uses secondary particles; the second positive electrode active material uses primary particles, which has better kinetic performance.

[0250] According to the solution of the embodiment of the present application, the inventors of this field have studied the particle size (D V 50) is tested, if the particle size of the material (D V 50) If the conditions described in this application are met, a layered structure design (rather than mixing in the same layer) can be preferably adopted to improve the dynamic performance.

[0251] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises at least two positive electrode active material layers; The two adjacent positive electrode active material layers include a first positive electrode active material and a second positive electrode active material respectively; the average particle size D of the first positive electrode active material V 50 is R1, the average particle size D of the second positive electrode active material V 50 is R2, and R1 and R2 satisfy the following relationship: R1≥5R2.

2. The positive electrode sheet according to claim 1, characterized in that: 50R2≥R1≥5R2, preferably 35R2≥R1≥5R2.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The value range of R1 is 2 μm-20 μm; optionally, the value range of R1 is 5 μm-15 μm.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The value range of R2 is 0.2 μm-12 μm; optionally, the value range of R2 is 0.2 μm-3.6 μm.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The first positive electrode active material has 5 μm≤D V 90-D V 10≤20μm; Optionally, in the first positive electrode active material, 9≤D V 90-D V 10≤20μm; Optionally, the second positive electrode active material has 5 μm≤D V 90-D V 10≤9μm.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The thickness of the positive electrode active material layer where the first positive electrode active material is located is H1; the thickness of the positive electrode active material layer where the second positive electrode active material is located is H2; The thickness of H2 accounts for 10%-70% of the total thickness of the positive electrode active layer of the positive electrode plate.

7. The positive electrode sheet according to claim 6, characterized in that: In terms of mass percentage, the first positive electrode active material includes 80%-100% of secondary particles.

8. The positive electrode sheet according to claim 6, characterized in that: In terms of mass percentage, the second positive electrode active material includes 95%-100% primary particles.

9. The positive electrode sheet according to claim 1, characterized in that: The first positive electrode active material includes a plurality of materials, and R1 is D of the plurality of materials. V 50; or, The second positive electrode active material includes a plurality of materials, and R2 is Dv50 of the plurality of materials.

10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The first positive electrode active material includes a layered structure positive electrode material.

11. The positive electrode sheet according to claim 10, characterized in that: The first positive electrode active material includes at least one of a nickel-cobalt-manganese-lithium ternary material, a nickel-cobalt-aluminum-lithium ternary material, and a nickel-cobalt-manganese-aluminum-lithium ternary material, or at least one of doped or coated materials including the above ternary materials.

12. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The second positive electrode active material includes at least one of a spinel structure positive electrode material or an olivine structure positive electrode material.

13. The positive electrode sheet according to claim 12, characterized in that: The second positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, and modified doped lithium iron manganese phosphate; Optionally, the chemical formula of the modified doped lithium manganese iron phosphate includes: LiMPO4, where M includes Mn and non-Mn elements; Optionally, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping; Optionally, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; Optionally, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg; Optionally, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N; Optionally, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N; Optionally, the second positive electrode active material includes Li a A e Mn 1-f B f P 1-g C g O 4-n D n ; Wherein, the A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; The B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; The C includes one or more elements selected from B, S, Si and N; The D comprises one or more elements selected from the group consisting of S, F, Cl and Br; The a is selected from the range of 0.9 to 1.1, the e is selected from the range of 0.001 to 0.1, the f is selected from the range of 0.001 to 0.5, the g is selected from the range of 0.001 to 0.1, the n is selected from the range of 0.001 to 0.1, and the second positive active material is electrically neutral.

14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The positive electrode sheet includes a current collector; The at least two positive electrode active material layers are stacked in sequence and formed on the surface of the current collector, and the porosity of the at least two positive electrode active material layers decreases in sequence in a direction away from the current collector.

15. The positive electrode sheet according to claim 14, characterized in that: The porosity of the positive electrode active material layer contacting the current collector is ≥45%; optionally, the porosity of the positive electrode active material layer contacting the current collector is ≥60%.

16. The positive electrode sheet according to claim 14, characterized in that: The porosity of the outermost layer of the positive electrode active material layer is ≥35%; optionally, the porosity of the outermost layer of the positive electrode active material layer is ≥50%.

17. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 16.

18. An electrical device, characterized in that: The electrical device comprises the battery according to claim 17.

Citation Information

Cited By

  • Coated ternary material doped with different particle sizes, preparation method thereof and battery

    CN120637473A